2016
DOI: 10.1016/j.mambio.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A re-assessment of Rensch's rule in tuco-tucos (Rodentia: Ctenomyidae: Ctenomys) using a phylogenetic approach

Abstract: Keywords:Body mass Model II regression Phylogenetic reduced major axis Scaling Sexual size dimorphism a b s t r a c t Sexual size dimorphism (SSD) is affected by a large number of factors, mating system being one of the most relevant. Almost 70 species of subterranean rodents of the genus Ctenomys are considered highly polygynic, and polygyny jointly with absence of paternal care of the young, favours high SSD. In this respect, Rensch's rule predicts that SSD scales with body size so that when males are larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 76 publications
3
26
0
Order By: Relevance
“…Our results have shown that two emblematic domesticated species, the dog and the cat follow a sexual dimorphism trend in size that conforms to the empirical pattern known as Rensch's rule which is not present at the interspecific level in their respective families (Martínez et al, 2014;Bidau, Martínez, 2016). We have also demonstrated that in dogs, body size variation and SSD between breeds vary more than in the Canidae as a whole, while cats show a much lower size variation than that of the Felidae but SSD variation between breeds is comparable to that of the whole family.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Our results have shown that two emblematic domesticated species, the dog and the cat follow a sexual dimorphism trend in size that conforms to the empirical pattern known as Rensch's rule which is not present at the interspecific level in their respective families (Martínez et al, 2014;Bidau, Martínez, 2016). We have also demonstrated that in dogs, body size variation and SSD between breeds vary more than in the Canidae as a whole, while cats show a much lower size variation than that of the Felidae but SSD variation between breeds is comparable to that of the whole family.…”
Section: Discussionsupporting
confidence: 70%
“…SSD tends to have low or no phylogenetic signal (Martínez et al, 2014;Stevens, Platt, 2015;Bidau, Martínez, 2016;Martínez, Bidau, 2016), and as said above there is no convincing mechanism to explain Rensch's rule or its frequent inversion. The possible reason is that so many mechanisms are involved in the production of SSD that a single trend in scaling of SSD with body size does not exist.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations